Is day-surgery laparoscopic cholecystectomy contraindicated in the elderly? Results from a retrospective study and literature review. (September 2016) - Carlomagno, Nicola; Tammaro, Vincenzo; Scotti, Alessandro; Candida, Maria; Calogero, Armando; Santangelo, Michele L.
Abstract: Background and aim: Ideally, day-surgery laparoscopic cholecystectomy (DLC) combines patient satisfaction with cost-effectiveness. However, DLC has not yet been widely applied in the elderly. Thus, to challenge the current perception of DLC as a contraindication, several parameters were investigated for the feasibility of DLC within the general and elderly population. A retrospective study was conducted to analyse age, along with other relevant patient characteristics, as factors leading to successful 24-h discharge. Methods: Data were collected from 207 patients who underwent laparoscopic cholecystectomy (LC) between 2010 and 2013. Of these patients, 154 were aged <75 years and 53 > 75 years, with a median age of 59.3 years. Comparisons of the length of post-surgical hospital stay were made. Further, the parameters influencing the surgeon's decision to discharge patients within a 24-h period were investigated: demographic data; patient characteristics such as age, sex and concomitant diseases; disease presentation; surgical experience; intraoperative complications; and post-operative course. The numbers of hospital readmissions and reoperations were established as parameters of failure. Results: Forty-five (21.7%) patients remained hospitalized up to 24 h. The majority of them had no co-morbidities, low American Society of Anesthesiologists (ASA) grades, adenomas and uncomplicated gallstone disease. Eleven patients were aged >75 years. None of the patients died, whereas one patient was readmitted following DLC. Considerations: Age itself did not prove to be a contraindication for DLC. The patient's general health, disease presentation and the surgeon's attitude were the main factors favouring early discharge. Patient selection and patient-care facilities were crucial for successful outcomes. Some problems due to the logistical organization of the hospital and the surgical approach, which may impede DLC acceptance, are described herein.